Defaults, Normative Anchors and the Occurrence of Risky and Cautious Shifts - Stephan Jagau; Theo Offerman (Tinbergen Institute, 2017)
Choice shifts occur when individuals advocate a risky (safe) decision when acting as part of a group even though they prefer a safe (risky) decision when acting as individuals. Even though research in psychology and economics has produced a mass of evidence on this puzzling phenomenon, there is no agreement about which mechanism produces choice shifts. In an experiment, we investigate the performance of two prominent mechanisms that have been proposed to explain the phenomenon; (i) rank-dependent utility and (ii) a desire to conform to the wishes of the majority. The evidence provides clear support for the conformity explanation.
Keywords: D03; D71; D81; 330; risky shift; cautious shift; conformity; diffusion of responsibility; rank-dependent utility